Effectiveness of Education on Providing Complementary Feeding Textures Appropriate to Toddlers' Ages for Stunting Prevention - Susilowati, Prima Endang; Listyawardhani, Yana; Betaditya, Dika; Ghaffar, Mufti; Sukmawati, Heni (Sarana Ilmu Indonesia (salnesia), 2025)
Failure to thrive in children is influenced by the quality of food consumed. Children aged six months and above require complementary feeding as a nutritional supplement, which should be prepared with texture suitable for their age to ensure digestibility. Local fish, containing low allergencity protein, is a recommended choice for complementary feeding. This activity aimed to enhance knowledge among mothers of toddlers, particularly those with children aged 6–12 months, about complementary feeding using local ingredients. The participants were mothers active in Naluri Posyandu and Kencana Posyandu in Panglayungan Village, Tasikmalaya City. The method involved stages of activity, including (1) monitoring child weight and (2) providing nutritional education on complementary feeding. The nutritional status monitoring showed that 20,00% of toddlers in Naluri Posyandu were stunted, with 9,00% severely stunted. While in Kencana Posyandu, 21,00% were stunted and 6,00% severely stunted. Through educational activities, mothers’ knowledge significantly improved, with pretest scores averaging 5.87 and posttest scores 8.02. The Wilcoxon test confirmed a significant difference in knowledge before and after intervention (p-value =0,000, p-value <0,05). This program had a positive impact on enhancing maternal knowledge. It is recommended that posyandu continue regular educational activities on complementary feeding and related topics, either through posyandu cadres or in collaboration with relevant institutions.